The Effect on Mortality of Bacterial Co-Infections on Critically Ill Patients with Community-Acquired COVID-19 and Influenza Pneumonia: A Systematic Review - Apostolos A. Menis; Efrosyni Gerovasileiou; Konstantinos Mantzarlis; Efstratios Manoulakas; Konstantina Deskata; Vasileios Vazgiourakis; Demosthenes Makris; George Dimopoulos (Viruses, 2025)
Background: Bacterial co-infections in patients with viral pneumonia might increase mortality. In this study we aimed to evaluate their effect on the mortality of critically ill patients with viral pneumonia. Methods: A systematic search was conducted in PubMed, Web of Science, Scopus and Cochrane from inception until 30 March 2025. We included studies comparing the effect on mortality of bacterial co-infections in critically ill patients with viral pneumonia. The risk of bias was assessed by the Newcastle–Ottawa Scale. Results: From 3643 studies, 10 were included in our study with a total of 2862 COVID-19 patients and 4573 influenza patients. Seven studies were retrospective and three prospective. In total, 359/2862 of the COVID-19 and 904/4573 of the influenza patients were co-infected. Co-infections increased mortality in five out of the six studies evaluating COVID-19 patients and in two out of the eight studies evaluating influenza patients. Conclusions: The majority of the included studies were retrospective, which may limit the accuracy of these results. The exclusion of non-English literature may have led to the omission of relevant data. Based on our results, the impact of bacterial co-infection may be more pronounced in patients with COVID-19 pneumonia admitted to the ICU than in patients with influenza pneumonia.